2008
DOI: 10.2522/ptj.20080036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Perception, Balance Perception, Fall History, Balance Performance, and Gait Speed on Walking Activity in Older Adults

Abstract: The measure of physical activity used in this study included only walking, not other low- to moderate-intensity activities that are common in older adults. Health and balance perception and gait speed were associated with walking activity more so than fall history or balance performance after controlling for potential confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 58 publications
1
30
2
Order By: Relevance
“…Although poor balance perception has been previously correlated with slower walking speed and fewer walking activities (Talkowski et al, 2008) and balance training has been shown to improve stance symmetry (Shumway-Cook et al, 1988;Winstein et al, 1989;Nichols, 1997;Sackley and Lincoln, 1997), our results showed that balance deficits, as measured as sway during eyes-closed standing, did not correlate with gait asymmetry. It is possible that stroke survivors do not have an accurate perception of their balance, which could discourage them from participating in walking activities.…”
Section: Discussioncontrasting
confidence: 77%
“…Although poor balance perception has been previously correlated with slower walking speed and fewer walking activities (Talkowski et al, 2008) and balance training has been shown to improve stance symmetry (Shumway-Cook et al, 1988;Winstein et al, 1989;Nichols, 1997;Sackley and Lincoln, 1997), our results showed that balance deficits, as measured as sway during eyes-closed standing, did not correlate with gait asymmetry. It is possible that stroke survivors do not have an accurate perception of their balance, which could discourage them from participating in walking activities.…”
Section: Discussioncontrasting
confidence: 77%
“…A relationship between SSWS and daily ambulatory activity was hypothesized given the measure’s association with ambulatory activity in individuals with stroke and incomplete spinal cord injury (Bowden et al, 2008; Perry et al, 1995; Stevens et al, 2013), as well as with self-reported levels of ambulatory activity in older adults (Talkowski, Brach, Studenski, & Newman, 2008). Although the relationship between MWS and daily ambulatory activity has received less attention, we hypothesized that MWS would also be predictive of steps per day based on the association between MWS and health status and physical activity in older adults (Sallinen et al, 2011; Sartor-Glittenberg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…-The way we move is also affected by our emotions. Depression has been found a co-factor for the risk of falling in the elders (Skelton and Todd, 2007;Talkowski et al, 2008), whereas somatisation, anxiety and depression were found intrinsic co-factors in non-specific musculoskeletal spinal disorders (Andersson, 1999). -Even if the optimal control assumption is acceptable for normal subjects, does it remain acceptable when used to model specific patients that are known to have neuromotor deficiencies?…”
Section: Introductionmentioning
confidence: 95%